Manifestasi Okular Coronavirus Disease 2019 (COVID-19): Klinis dan pencegahan - Priscilia, Florentina; Iskandar, Ferdy; Larasati, Fadima Fitri; Permanik, Gustiandari Fidhya (PT. Kalbe Farma Tbk., 2020)
Pandemi global Coronavirus Disease 2019 (COVID-19) memiliki gejala utama batuk, demam, kelelahan, sesak napas, dan gejala respiratori lainnya. Didapatkan kasus pasien COVID-19 yang memiliki keluhan okular seperti konjungtivitis. Angiotensin-converting enzyme 2 (ACE2), yang merupakan reseptor SARS-CoV-2 juga didapatkan pada sel epitel konjungtiva dan kornea manusia, sehingga memungkinkan transmisi melalui okular. Tatalaksana gejala okular pada COVID-19 hingga saat ini masih terus dikembangkan serta diuji coba.The Global Coronavirus Disease 2019 (COVID-19) pandemic has cough, fever, fatigue, shortness of breath, and other respiratory symptoms as the main symptoms. There were cases of COVID-19 patients with ocular complaints such as conjunctivitis. Angiotensin-converting enzyme 2 (ACE2) – SARS-CoV-2 receptor, is also found in human conjunctival and corneal epithelial cells, thus allowing ocular transmission. Treatment for ocular symptoms in COVID-19 are still being developed and tested.